A Novel TRAF3IP2 Mutation Causing Chronic Mucocutaneous Candidiasis - Marujo, F (2021)
nborn errors of the IL-17-mediated signaling have been associated with chronic mucocutaneous candidiasis (CMC). We describe a patient with CMC, atopic dermatitis, enamel dysplasia, and recurrent parotitis harboring a novel compound heterozygous mutation of TRAF3IP2, leading to autosomal recessive ACT1 deficiency and deficient IL-17 signaling.